PENERAPAN MODEL B2B PADA SISTEM INFORMASI BERBASIS WEB (STUDI KASUS PT SEMEN BATURAJA PERSERO) - Fardinal Maidoni; Endang Lestari Ruskan; Apriansyah Putra (Universitas Sriwijaya, 2010)
E-commerce can be utilized by various parties to improve its business processes like enterprise. PT Semen Baturaja (Persero) is one company engaged in the cement industry in South Sumatra. PT Semen Baturaja is relevant places in this study because of inadequate human resources and technology to implement e-commerce model. E-commerce model was developed in PT Semen Baturaja (Persero) is a model of B2B (Business to Business). B2B model integrating between companies, partners, suppliers and distributors. The method used in this study is the method of system development FAST (Framework for the Application of Systems Techniques) with a prototyping approach. Â Kata kunci : e-commerce model B2B (Business to Business), PT Semen Baturaja (Persero), FAST (Framework for the Application of Systems Techniques)